Kajian Penyebaran Inovasi Teknologi Serealia Melalui Pameran (Jurnal Perpustakaan Pertanian, 2013)
Study on Dissemination of Cereal Technology InnovationThrough ExhibitionExhibition of Cereal Technology Innovation was one of the activitiesto disseminate the research results to the users. The exhibition washeld on the occasion of the National Cereal Week in Maros, SouthSulawesi on 26-30 July 2010. The purpose of the study was to findout the user’s perception on the supporting materials displayed(materials of the technology innovation), stand guides, the layout ofthe stand, and the satisfaction of the visitors of the whole exhibitionorganization, as well as to obtain the feedbacks for the actual needsof the users and the improvement for the next exhibition. The resultsshowed of 107 visitors as respondents, 84.12% of them expressed thematerials displayed were relevant with the theme of the exhibitionand 73,83% said they fit to the needs. Almost all respondents saidthat the materials were sufficiently up-to-date and interesting and thestand guides were able to give information related to materialsdisplayed. In addition, 98.13% of the respondents perceived thestand decoration was interesting and all respondents expressed theirsatisfaction of sufficiently satisfied, satisfied and very satisfied overthe materials. The feedbacks reflected the importance of supportingdisplayed materials in multimedia formats and demonstration,enhancing the quality and quantity of the guides as well as moresocializing or promoting the exhibition so as to more farmers andsociety at large visit the exhibition in order to reach the expectedtargets.
Keywords: Technology innovation; information dissemination; exhibition; material displayed